Cigarette Smoking Before and After Breast Cancer Diagnosis: Mortality From Breast Cancer and Smoking-Related Diseases - Passarelli, Michael N. (J Clin Oncol, 2016)
PURPOSE: Cigarette smoking increases overall mortality, but it is not established whether smoking is associated with breast cancer prognosis. METHODS: We evaluated the association between smoking status before and after breast cancer diagnosis and mortality in the Collaborative Breast Cancer and Women’s Longevity Study, a population-based prospective observational study conducted in Wisconsin, New Hampshire, and Massachusetts. Participants included 20,691 women, ages 20 to 79 years, diagnosed with incident localized or regional invasive breast cancer between 1988 and 2008; a subset of 4,562 of these women were recontacted a median of 6 years after diagnosis. Hazard ratios (HRs) with 95% CIs were calculated according to smoking status for death as a result of breast cancer; cancers of the lung, pharynx, or intrathoracic organs; other cancer; respiratory disease; and cardiovascular disease. RESULTS: During a median of 12 years, 6,778 women died, including 2,894 who died as a result of breast cancer. Active smokers 1 year before breast cancer diagnosis were more likely than never smokers to die of breast cancer (HR, 1.25; 95% CI, 1.13 to 1.37), respiratory cancer (HR, 14.48; 95% CI, 9.89 to 21.21), other respiratory disease (HR, 6.02; 95% CI, 4.55 to 7.97), and cardiovascular disease (HR, 2.08; 95% CI, 1.80 to 2.41). The 10% of women who continued to smoke after diagnosis were more likely than never smokers to die of breast cancer (HR, 1.72; 95% CI, 1.13 to 2.60). When compared with women who continued to smoke after diagnosis, those who quit smoking after diagnosis had lower mortality from breast cancer (HR, 0.67; 95% CI, 0.38 to 1.19) and respiratory cancer (HR, 0.39; 95% CI, 0.16 to 0.95). CONCLUSION: Smoking before or after diagnosis was associated with a higher mortality from breast cancer and several other causes.